2021
DOI: 10.1111/hsc.13312
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy behaviours in urban Illinois communities affected by eviction: A descriptive analysis

Abstract: Eviction of renter-occupied homes is an emerging public health crisis adversely impacting populations already at risk. Although housing quality and home-owner foreclosures have been linked to health outcomes, the relationship between eviction of renter-occupied homes and health has not been well established. The demographics and socioeconomic status of renters differs from homeowners, as such any relationship with health outcomes should be distinguished between the two. The aim of this study is to provide a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In addition, cost-driven moves may necessitate compromises (eg, working more hours, reducing certain expenses, or moving to lower-quality housing or a less desirable neighborhood) that further diminish opportunities for health promotion and social connection, ultimately limiting both general health and physical activity . Although previous research has found an ecological association between neighborhood eviction rates and lower participation in leisure-time exercise, our study is the first, to our knowledge, to find an association between cost-driven moves and diminished physical activity at the individual level.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, cost-driven moves may necessitate compromises (eg, working more hours, reducing certain expenses, or moving to lower-quality housing or a less desirable neighborhood) that further diminish opportunities for health promotion and social connection, ultimately limiting both general health and physical activity . Although previous research has found an ecological association between neighborhood eviction rates and lower participation in leisure-time exercise, our study is the first, to our knowledge, to find an association between cost-driven moves and diminished physical activity at the individual level.…”
Section: Discussionmentioning
confidence: 61%
“…Six studies investigating the association between population-level eviction or foreclosure rates and weight produced mixed results. Hazekamp et al found that the prevalence of obesity, as well as other unhealthy behavior indicators (i.e., binge drinking, current smoking status, lack of leisure-time physical activity, and short sleep), was associated with census-level eviction rates in urban Illinois communities [ 87 ]. Another cross-sectional study found that foreclosures in 75 of the top 100 most populous metropolitan areas in the United States were independently associated with obesity prevalence [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 b and d). Housing insecurity and unaffordability can lead to stress and despair, as well as alter metabolism and increase the risk of unhealthy behaviors such as smoking and inactivity (Chambers and Fuster 2012 ; Hazekamp et al 2021 ). Little is known about how policy interventions, such as supply-side housing subsidy programs aimed at increasing affordable housing, affect eviction dynamics in communities across the United States (Preston and Reina 2021 ).…”
Section: Discussionmentioning
confidence: 99%